Harmful Algal Blooms on the Portuguese coast: Cross-checking events with remote sensing ocean colour data for coastal management - Monteiro, Helena (2024)
Phytoplankton plays a vital role in marine ecosystems, serving as a primary food source for a diverse array of organisms, including commercially important bivalves, crustaceans, and fish. However, in some situations, the proliferation of algae can cause serious economic losses for aquaculture, fishing, and tourism and have major environmental and human health impacts. Increases in the occurrence of toxic phytoplankton blooms in Iberian waters have been reported. Earth Observation (EO) can provide important information about the spatial and temporal distribution and the destination of blooms, with scales not available for conventional monitoring techniques.